The House on August Street - Bargur, Ayelet (Eden Productions, 2008)
Verzio FF Submission “The House on August Street” tells the story of Beate Berger, a German Jew who single-handedly and with great resolve and vision rescued over 100 children during the Holocaust, smuggling them from Berlin to Palestine in the 1930s. Berger, founder of the House of Love Children’s Home (Beith Ahawah Kinderheim) Berlin’s first home for poor Jewish children, was quick to recognize the Nazi threat and resolved to protect the 120 children under her care on Auguststrasse 14-16. The film is based on the 2006 book “Ahawah Heisst Liebe”. Bargur’s innovative documentary weaves together rare archival film materials and interviews with Berger’s “children” with monologues based on Berger’s letters, narrated by German actress Naomi Krauss.